2021
DOI: 10.1101/2021.10.11.463897
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combined effects of bird extinctions and introductions in oceanic islands: decreased functional diversity despite increased species richness

Abstract: Aim: We analyse the functional consequences of the changes in species composition resulting from extinctions and introductions on oceanic island bird assemblages. Specifically, we ask if introduced species have compensated the functional loss resulting from species extinctions. Location: Seventy-four oceanic islands (>100 km2) in the Atlantic, Pacific and Indian Oceans. Time period: Late Holocene. Major taxa studied: Terrestrial and freshwater bird species. Methods: We compiled a species list per island (ex… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…In addition, an analysis of avian extinctions in the Hawaiian Islands found that species that went extinct in prehistoric times (i.e., prior to European contact) tended to be large‐bodied, whereas those in historic times (i.e., after European contact) tended to be mid‐sized species, possibly because the most vulnerable large‐bodied species had already been lost (Boyer, 2008). However, in our null model and individual trait comparison analyses, we found that larger‐bodied island endemic species were more likely to be threatened and to have gone extinct (see also Fromm & Meiri, 2021; Soares et al, 2022). This result could illustrate that hunting, which typically targets larger‐bodied bird species (e.g., Duncan et al, 2002, 2013), is the most pervasive threat on islands, or it could be that the traits that tend to correlate with body size (low reproductive rates, low rates of population growth, small population sizes, small clutch size, long intervals between clutches, larger home ranges; Boyer, 2008; Gaston & Blackburn, 1995) are driving this pattern.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…In addition, an analysis of avian extinctions in the Hawaiian Islands found that species that went extinct in prehistoric times (i.e., prior to European contact) tended to be large‐bodied, whereas those in historic times (i.e., after European contact) tended to be mid‐sized species, possibly because the most vulnerable large‐bodied species had already been lost (Boyer, 2008). However, in our null model and individual trait comparison analyses, we found that larger‐bodied island endemic species were more likely to be threatened and to have gone extinct (see also Fromm & Meiri, 2021; Soares et al, 2022). This result could illustrate that hunting, which typically targets larger‐bodied bird species (e.g., Duncan et al, 2002, 2013), is the most pervasive threat on islands, or it could be that the traits that tend to correlate with body size (low reproductive rates, low rates of population growth, small population sizes, small clutch size, long intervals between clutches, larger home ranges; Boyer, 2008; Gaston & Blackburn, 1995) are driving this pattern.…”
Section: Discussionmentioning
confidence: 71%
“…First, it does not include species that went extinct as a result of human actions prior to 1500 CE. Pre‐1500 CE human communities are known to have caused a large number of avian extinctions on islands through hunting, the introduction of non‐native species and habitat loss (Boyer, 2008; Duncan et al, 2013; Hume, 2017; Milberg & Tyrberg, 1993; Russell & Kueffer, 2019; Sayol et al, 2020; Soares et al, 2021, 2022; Steadman, 2006; Szabo et al, 2012; Whittaker & Fernández‐Palacios, 2007; Table 1). Indeed, we found evidence of at least 307 pre‐1500 CE island endemic extinctions (i.e., the 8% extinct figure increases to 22% if we include all known island endemic bird extinctions).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When climate change is combined with other impacts of increasing human population size and economic development, such as habitat modification and degradation, the challenge for managing and conserving insular biodiversity presents itself as being immediate and largescale (Russell & Kueffer, 2019). It is not only the loss of species and their interactions that is particularly relevant on islands, but also the loss of unique evolutionary history (phylogenetic and functional diversity), reflecting the loss of unique adaptations to the environment (Sayol et al, 2021;Soares, de Lima, Palmeirim, Cardoso, & Rodrigues, 2021).…”
Section: Introductionmentioning
confidence: 99%